Benefits and Barriers of Holistic Nursing Training by High-Fidelity Simulation in Obstetrics. (28th June 2022) - Zhang, Wenxi; Lozynska, Inna; Li, Wei; Cai, Nana; Yang, Hongmin
Abstract : Background . With t he technology of high-fidelity simulates developed, the clinical education route has changed. The nursing school pays attention on the use of high-fidelity simulations in nursing education. However, in China, only a few schools can afford the expensive teaching tools, including SimMom 3G and virtual reality (VR) devices, which also focus on "holistic nursing simulation." Objective . To explore the evaluation and development of a holistic nursing simulation session for nursing students based on an integrated nursing approach in obstetrics. Methods . This study was based in a rich Chinese nursing school under the medical university that value nursing education. This study is founded on 147 third-year nursing students in obstetrics classes. After the simulation teaching, the teaching effect of the questionnaire was investigated, and the total number of questionnaires was 124 students. Results . Students agreed that the holistic nursing simulation cultivated humanistic care literacy, clinical practice ability, and clinical thinking ability; enhanced teamwork ability; and reinforced professional knowledge. Conclusion . This simulation teaching method helps to cultivate students' enthusiasm and initiative and fosters their self-learning ability.